Terahertz-Time Domain Spectroscopic (THz-TDS) Measurement of Moderately-Doped Silicon Using InAs Emitter Under Magnetic Field - Quema, A.; Migita, M.; Nashima, S.; Hangyo, M. (Science Diliman: A Journal of Pure and Applied Sciences; Vol 13 No 2 (2001), 2012)
The complex refractive index of silicon using terahertz-time domain spectroscopy (THz-TDS), with an InAs wafer under the influence of a magnetic field as emitter, has been studied. By applying a magnetic field on the InAs emitter, the detected temporal waveform broadens and the spectral weight of its Fourier spectrum shifts toward the low frequency region. Calculating the real (n) and imaginary (κ) parts of the complex refractive index of silicon, it is found that with the application of a magnetic field the plots of these quantities in the low frequency region (sub-terahertz region) are smoother than those without magnetic field. These features indicate that a significant enhancement of the signal-to-noise (S/N) ratio in the low frequency can be obtained by applying a magnetic field on the InAs emitter.